Which students need accommodations the most, and to what extent are their needs met by regular upper secondary school? A cross-sectional study among students with special educational needs. Issue 3 (27th May 2019) - Yngve, Moa; Lidström, Helene; Ekbladh, Elin; Hemmingsson, Helena
ABSTRACT: The aim of this study was twofold: (1) to identify factors associated with a high level of accommodation needs in school activities among students with special educational needs (SEN) in regular upper secondary education; and (2) to investigate the extent to which schools have met students' perceived accommodation needs. Accommodation needs and their provision in school activities were assessed with the School Setting Interview for 484 students with SEN. Students' mean age was 17.3 years and 50% did not have a diagnosis. A logistic regression analysis revealed that a high level of school absence, studying a vocational programme, and a neuropsychiatric disorder were associated with a high level of accommodation needs. In the majority of school activities, about 50% of students had not received any accommodation despite an experienced need for support. About 30% of students perceived a need for support even though they had been provided with accommodations, and around 25% stated they were satisfied with received accommodations. Regular upper secondary school students with SEN are insufficiently provided with accommodations to satisfactorily participate in education. Specific student characteristics, e.g. high level of school absence, should receive special attention when investigating and accommodating students' needs for support in school activities.